Daya Antibakteri Infusa Kulit Manggis (Garcinia mangostana L) terhadap Streptococcus mutans (Antibacterial of Mangosteen peel infuse (Garcinia mangostana L ) Against Streptococcus mutans) - Muhamad Martin Widayat; Purwanto Purwanto; Amandia Dewi Permana Shita (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
One of the main causes of dental caries is Streptococcus mutans. Some sourcesmentioned in the mangosteen peel contains flavonoids, saponins and tannins whichhave antibacterial activity. The purpose of this research was to determine theantibacterial activity of mangosteen peel infuse against S.mutans, the most effectiveinhibition and minimum inhibition. The sample was divided into 10 groups: negativecontrol (K), positive control (K +), and the treatment group of infusa mangosteen rindwith concentration of 100%, 50%, 25%, 12.5%, 6.25%, 3.13%, 1.56% and 0.78%.Negative control group only containing BHI-B. Positive control group containing BHI-B,S.mutans and Tetracycline hydrochloride. The treatment groups containing BHI-B, S.mutans and different concentration of each group. S.mutans colonies was counted usinga colony counter. Data were analyzed with the Kruskal Wallis test followed by Mann-Whitney test. Results of this research showed that infuse mangosteen rind was effectiveas an antibacterial. The most effective concentration which can inhibit S.mutans colonieswas 100% and the minimum concentration was 0.78%.Keywords: Mangosteen peel infuse, antibacteria, Streptococcus mutans, Tetracycline